Efektivitas Model Problem Based Learning Mata Pelajaran Geografi Materi Pokok Ketahanan Pangan, Energi, dan Industri di Kelas XI SMA Negeri 3 Pekalongan - Lestari, Mugi; Suharini, Erni; Banowati, Eva (Edu Geography, 2018)
The purpose of this research is to determine the effectivity of studying geography using problem based learning model to the students learning outcomes and positive responses of student to studying geography that uses problem based learning model. The experimental research done with quarsy experimental design model. Sampling method that used is purposive sampling with XI IPS 2 as experimental class and XI IPS 1 as a control class. Data collecting technique that used is test, questionnaires, observation, and documentation. Analysis data technique that used is normalized gain test and descriptive percentage. The result is: 1) studying geography with problem based learning model is effective to improve students learning outcomes. The cognitive study result in experiment class raised to 0.43 and include to âaverageâ category. The affective and psychomotor study in experiment class is better than control class with âexcellentâ category. The study result in experiment class are better because of student got a direct experience in studying, so the knowledge that students have arenât textual, but also more better understanding. 2) the student response to positive learning, include to âvery agreeâ category. The conclusion of this research is problem based learning model is effective to use in studying geography on food security subject Tujuan penelitian ini adalah untuk mengetahui efektivitas pembelajaran geografi menggunakan model problem based learning terhadap hasil belajar siswa dan respon positif siswa terhadap pembelajaran geografi menggunakan model problem based learning. Penelitian eksperimen yang dilakukan menggunakan model quarsy experimental design dengan rancangan nonequivalent control group design. Metode pengumpulan sampel yang digunakan adalah purposive sampling dengan sampel kelas XI IPS 2 sebagai kelas eksperimen dan kelas XI IPS 1 sebagai kelas kontrol. Teknik dalam pengumpulan data yang digunakan yaitu test, kuisioner, observasi, dan dokumentasi. Teknik analisis data yang digunakan adalah uji normalized gain dan deskriptif persentase. Hasil penelitian: 1) Pembelajaran geografi menggunakan model problem based learning efektif untuk mengingkatkan hasil belajar siswa. Hasil belajar kognitif siswa di kelas eksperimen mengalami peningkatan sebesar 0,43 dan masuk kedalam kategori âSedangâ. Hasil belajar afektif dan psikomotorik siswa di kelas eksperimen lebih baik dibandingkan kelas kontrol dengan kategori âsangat baikâ. Hasil belajar kelas eksperimen lebih baik karena dalam pembelajaran siswa mendapatkan pengalaman langsung, sehingga pengetahuan yang diperoleh siswa tidak hanya tekstual, namun pemahaman yang lebih luas. 2) Respon siswa terhadap pembelajaran positif, masuk kedalam kategori âsangat setujuâ. Simpulan penelitian ini adalah model problem based learning efektif diterapkan dalam pembelajaran geografi materi ketahanan pangan.